ANALISIS PENGARUH SELF EFFICACY TERHADAP KEMAMPUAN KONEKSI MATEMATIK SISWA SMP PADA MATERI BANGUN RUANG SISI DATAR - Zakiyah Mukhtari; Anik Yuliani; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to analyze the effect of self efficacy on the mathematical connection ability of junior high school students on the material on flat side spaces. The method used is descriptive qualitative method. This study took the subjects of class IX A, 26 students from SMPN 1 Parongpong, West Bandung Regency. This research instrument was in the form of mathematical connection ability questions, self efficacy questionnaires, and interviews. After doing the research, it is concluded that in general, there is an effect of self efficacy on students' mathematical connection abilities. Students who have high mathematical connection ability are students with high self efficacy categories. In general students who have low connection ability are students with low self efficacy category but there are some students with low self efficacy category who have high mathematical connection ability.